FAKTOR-FAKTOR YANG MENJADI KENDALA DALAM PEMBERIAN BANTUAN HUKUM SECARA CUMA-CUMA (PRODEO) DALAM PERKARA PIDANA DI PENGADILAN NEGERI DI SAMARINDA. - Hekki Purnama Setia (Universitas 17 Agustus 1945 Samarinda, 2014)
ABSTRACT There is so many people who cannot afford and who didn’t know sifgnificance of the role of legal aid, Because they didn’t know what and how to get a legal aid. But actually when they know efforts what to do it’s not too difficult. They simply declared incapable by accompanied a letter from neighborhood association, chief of police, the head of prosecutor’s office, and head of social and political. The existence of factors that become obstacles to implementation of legal aid free of charge, among them : don’t dare to ask suspects the presence of legal counsel at the level of investigation, fear because incapable to pay, suspects was resigned to and feel guilty, the investigators found the presence of legal counsel could be a obstacle in the process of interogation in making news of the proceedings, the limited time and condition that sometimes is not possible as well as the limited funds. Still so many people caught a criminal offence who does not get the right to obtain legal assistance or accompanied by a legal advisor in all levels of the process of investigation a result of the negligence of the officials concerned. It is in a known future. The vedict has been set by the judge at the time ago will be annulled by law and suspect has the right to be free from all claims submitted to him